Ten years of translation : proceedings of the fourth congress of the International Federation of Translators (FIT), Dubrovnik 1963, held in celebration of the tenth anniversary of the Federation = Dix annees de traduction - Citroen, I. J. (Congres de la Federation internationale des traducteurs, 1967)
Ten Years of Translation documents the proceedings of the Fourth Congress of the International Federation of Translators (Fidiration Internationale des Traducteurs-FIT) held in Dubrovnik in 1963.